Pengaruh Kompetensi Profesional Tutor terhadap Hasil Belajar pada Kursus Setir Mobil di LKP SAHARA Kab. Demak - Ella Anggraini; Tri Suminar (Journal on Education, 2024)
This research aims to (1) determine the influence of tutors' professional competence on participants' learning outcomes in car driving courses (2) the percentage influence of tutors' professional competence on trainees' learning outcomes. The research that researchers will use is quantitative research with an associative ex post facto approach. Data collection used a questionnaire in the form of a Google form link which was distributed to the research sample. Determination of the sample size in this study was based on a sampling technique using probability random sampling, so that a sample of 80 graduates participating in car driving training at LKP SAHARA was obtained. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis with simple linear regression analysis. This research shows results (1) that the tutor's professional competence has a significant effect on learning outcomes in car driving courses. (2) the percentage influence of the tutor's professional competence on learning outcomes in the car driving course at LKP SAHARA is 26.7%. In the research used only 1 variable where the results were 26.7% of the Adjusted R Square and 73.3% were influenced by other variables.